NOTARY RESPONSIBILITY FOR THIRD PARTY LOSSES DUE TO THE ISSUANCE OF THE DEED OF BINDING OF LAND PURCHASE AGREEMENT - Halimi, Halimi (TRUNOJOYO LAW REVIEW, 2023)
Third parties in the formation of the Deed of Sale and Purchase Agreement Land have rights to the object regulated in the PPJB even though they are not involved in its formation as long as they have legal ties to the object being agreed upon. When a material loss occurs to a third party originating from the issuance of the PPJB, does the notary have the responsibility to compensate for the loss or vice versa? This type of legal research is a type of normative legal research. The results of this study indicate that legal remedies that a third party can take if the deed of binding sale and purchase agreement issued by a notary causes harm to him is to send a subpoena, carry out an unlawful act lawsuit, report an alleged criminal act and make a complaint to the Regional Supervisory Council. The form of liability that a Notary can bear for the issuance of the Deed of Sale and Purchase Binding Agreement which is detrimental to third parties is civil liability by compensating for losses suffered by third parties by the provisions of Article 1365 of the Civil Code and criminal liability, namely serving a criminal sentence following the criminal provisions in Article 263 paragraph (1) and (2) or 264 or 266 of the Indonesian Criminal Code and ethically responsible according to Article 85 by receiving administrative sanctions.